A Pathophysiological Approach to Understanding Pulmonary Hypertension in Cardiac Surgery - Nguyen, Anne Q. N.; Deschamps, Alain; Varin, France; Perrault, Louis P.; Denault, André Y. (IntechOpen, 2012)
None